Dipeptidyl-peptidase-like protein 6 encephalitis treated with immunotherapy - Ye, Lan (Proc (Bayl Univ Med Cent), 2020)
This case describes a middle-aged man with anti-dipeptidyl-peptidase-like protein 6 (DPPX) encephalitis who exhibited the triad of memory loss, diarrhea, and tremor. The progression of his disease resembled neurodegenerative disease, and his first presentation at our department was 2 years after the first onset of symptoms. Antibodies against DPPX were positive in both serum and cerebrospinal fluid. No related tumor was found. The patient was initially treated with corticosteroid therapy and plasmapheresis. Despite moderate response to this treatment, corticosteroids were ceased because of adverse effects such as Cushing syndrome, deep vein thrombosis, and osteoporosis. After five cycles of treatment with rituximab, the patient experienced no further progression of neurologic symptoms and no adverse effects. The case adds to the understanding of the diagnosis, treatment, and potential prognosis of anti-DPPX encephalitis.